Analisis Metakomunikasi dalam Relasi Kepentingan Korporasi dan Politik: Studi Kasus Partai Perindo - Bachtiar, Alfan; Barizki, Rezzi Nanda; Misnan, Misnan; Pranawukir, Iswahyu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The nexus between corporations and politics in Indonesia is often characterized by the transformation of economic dominance into political influence, which risks undermining democratic principles. This study examines how metacommunication is strategically employed to establish legitimacy, shape public perception, and reinforce power relations between the Perindo Party and the MNC Group, its affiliated media conglomerate. The research aims to analyze the role of metacommunication in Perindo’s political strategy and its broader implications for Indonesian democracy. Using a qualitative case study approach, the study applies critical discourse analysis to the MNC Group’s media content alongside symbolic interpretation of Perindo’s political communication. Findings indicate that metacommunication through implicit messaging, symbolic repetition such as the “Mars Perindo” slogan, and nonverbal leadership imagery functions as an effective tool in projecting a pro-people image. However, the commodification of content, audiences, and media workers illustrates a shift of media from a public sphere to a personal political instrument, reinforcing media oligarchy and generating a democratic deficit. A parallel analysis of the 2025 SOE Law further demonstrates how metacommunicative framing produces divergent interpretations: the government presents it as efficiency-driven reform, while civil society perceives it as a threat to accountability. The study concludes that while metacommunication is a powerful strategy in corporate-political relations, it simultaneously exacerbates democratic vulnerabilities. Strengthening transparency, independent oversight, and regulatory frameworks is essential to safeguard accountability and democratic integrity in Indonesia.